Konsep Khatam Al-Nubuwwah dan Agama yang Sempurna - Ali, Abdul Karim (Jurnal Usuluddin, 2000)
Sayyid Abu al-Hasan 'Ali al-Nadwi in this book the Final Prophet dan the Perfect Religion attempts to promote the perfectness of Islam based on the concept of Khatam al-Nubuwwah-the finality of prophethood. There is a distinctive and distinguished concept in Islam pertaining to the finality of prophethood. The finality of prophethood prevents any claimant to prophecy as contrast to what had happened in Judaism and Chistianity. It also intends to repudiate and refute the teachings of Qadianism especially regarding to the claim of Mirza Ghulam Ahmad to prophecy. Part of the discussion based on Scriptures as well as history give light on the fortunateness of Islam compared to other religions as Judaism and Christianity. The article also touches on Buddhism in which it tried to abolish idolatry or worship of idols, but it ended with a religion that worships Buddha, its founder.